Tratamento de corantes reativos em solução aquosa utilizando lodo de esgoto sanitário como biossorvente em reatores contínuos. - Silva, Rene Pinto da (2012)
Conventional treatments of textile industry effluents usually produce significant amounts of recalcitrant subproducts. Among the new treatment technologies, adsorption appears as an alternative method. In this study, the efficiency of sewage sludge in the removal of reactive dye yellow GR, blue GN and red RB was evaluated to pH, total alkalinity, volatile fatty acids, acidity, electrical conductivity, turbidity, dissolved oxygen, total solids and absorbance in function of operation time. For this, the sludge were pre-treated at heat, powdered, sieved and placed in reactors continuous flow with and without aeration. The aerobic reactor showed appreciable amount of adsorption, 86% during 60 days, while in anaerobic reactor was about 81%. Adsorption of dyes by LES had been found to be dependent on pH of the solution, which increased in the pH around 5-7. The final results were promising, with respect to physico-chemical parameters measured, since the effluent after treatment was in accordance with current legislation in relation to the discharge of effluents into water bodies.